Conocimiento y manejo en tecnologías de la información y las comunicaciones (TIC) de profesores de medicina antes de COVID-19: KKnowledge and management of Information and Communications Technology (ICT) in medical teachers before COVID-19 (La U Investiga, 2024)
Introduction: Information and Communication Technologies (ICT) constitute a set of tools whose integration into our lives has transformed the way we access knowledge, information, and learning. Objective: To describe the knowledge and utilization of ICT among medical teaching staff prior to the COVID-19 health emergency. Method: This descriptive study involved the selection of 117 medical educators through non-probabilistic convenience sampling. Data were collected from surveys conducted in 2018, and data tabulation and analysis were carried out using measures of frequency and percentages with Microsoft Excel 2016 and Jamovi 2.3.19. Results: Before the health emergency, over half of the educators (52.99%) were familiar with and utilized ICT in their classes, while 41.88% used virtual classrooms. The most employed ICT tools by educators were online storage and sharing tools (43.59%), word processors (42.74%), presentation generation tools (41.88%), video editors, and virtual reality (33.33%), and WhatsApp in educational activities (31.62%). Nevertheless, 98.3% of the educators expressed a strong interest in receiving additional training. Conclusions: Prior to the health emergency, educators were knowledgeable and proficient in the use of ICT in their daily practices, including tools for online storage and sharing, word processors, presentation generators, and the WhatsApp application. Additionally, they are interested in continuing their training.
Keywords: Teaching; Teacher; Professor; Medicine; ICT; Higher education